2008
DOI: 10.1016/j.rasd.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypy in autism: The importance of function

Abstract: We argue for the utility of a functional definition of stereotypy based on evidence of both sensory automatic and socially mediated reinforcement contingencies in the occurrence of stereotypy in children with autism. A predetermined sensory function of stereotypy is often invoked in the behavioral literature and the term "self-stimulatory behavior" is commonly misused as interchangeable with "stereotypy." We discuss evidence for a variety of potential functional properties of stereotypy. Diagnostic definitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(155 citation statements)
references
References 40 publications
1
149
0
5
Order By: Relevance
“…Based on this information, decisions can be made about the best strategies to maximize welfare in each situation. As noted by Mason et al (2007), this approach is consistent with the applied behavior-analytic human treatment literature (e.g., Cunningham & Schreibman 2008;Shabani, Wilder, & Flood, 2001). Bassett and Buchanan-Smith (2007) reviewed the literature on predictability of environmental events in relation to animal welfare and concluded that unpredictable feeding can lead to increased exploration and other species-typical behavior.…”
Section: Enrichment Goals Strategies and Measuressupporting
confidence: 78%
“…Based on this information, decisions can be made about the best strategies to maximize welfare in each situation. As noted by Mason et al (2007), this approach is consistent with the applied behavior-analytic human treatment literature (e.g., Cunningham & Schreibman 2008;Shabani, Wilder, & Flood, 2001). Bassett and Buchanan-Smith (2007) reviewed the literature on predictability of environmental events in relation to animal welfare and concluded that unpredictable feeding can lead to increased exploration and other species-typical behavior.…”
Section: Enrichment Goals Strategies and Measuressupporting
confidence: 78%
“…In fact, of the 93.7% who engaged Risk factors for challenging behavior 15 in challenging behavior, only 3 did not engage in stereotyped behaviors. Stereotypy can be extremely inhibitory in the development of adaptive behavior, play skills and the acquisition of even simple discrimination tasks (Cunningham & Schreibman, 2007). Practitioners should be aware of such a high prevalence of stereotyped behaviors among children with autism and its repercussions, so that development of such behaviors can be prevented or decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Stereotypy is a form of self-stimulation and is illustrated by the practice of engaging in repetitive movements, often motoric or verbal, which does not appear contextually appropriate or with purpose (Cunningham & Schreibman, 2008). Additionally, the practice of stereotypy often seems to result in internal reinforcement for the individual demonstrating it.…”
Section: Discussionmentioning
confidence: 99%